PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL)TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 10 PADANG - Ginting, Metamya Aisy; Yerizon, Yerizon (Jurnal Edukasi dan Penelitian Matematika, 2024)
All students need problem-solving skills. However, students still have difficulties in solving problems. Thus, a learning model that can develop students' ability to solve problems is needed. This study examines how Problem Based Learning (PBL) affects students' problem solving skills. This quantitative research used the Nonequivalent Posttest-Only Control Group Design. All eighth grade students from nine classes were studied. Two classes with 63 students were sampled. This study used random sampling at SMP Negeri 10 Padang. Data were collected using test questions. Data analysis showed that the t-test for hypothesis testing rejected the null hypothesis (H0) with a P-value of less than 0.05. The problem-based learning model has an effect on the mathematics problem solving ability of students in grade VIII of SMP Negeri 10 Padang.Keywords – Mathematical Problem Solving Ability, PBL, Conventional Learning